2016
DOI: 10.25215/0304.139
|View full text |Cite
|
Sign up to set email alerts
|

Social Support In Relation To Quality Of Life among Caregivers of Drug Addicted People

Abstract: Taking care of a dependent relative entails different physical, psychological and social changes for caregivers. One of the most affected aspects is the social network and support, due to the lack of opportunities for leisure activities, impossibility to go out to work and changes in family routines. Social support also could act as a moderator when it affects caregiver’s quality of life by altering the direction and/or strength of the relation between the caregiver and his/her quality of life. Thus, social su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“… 27 Moreover, Ahmad et al revealed a significant positive relationship between social support and the quality of life among the caregivers of drug-addicted people. 33 Social relationships were among the most affected aspects of life in the whole family of addicted patients due to reduced opportunities for leisure activities, changes in family routines, and difficulties encountered in working and meeting their colleagues. 33 Moreover, some addicts and caregivers chose social isolation as a tool to safeguard their reputation in society by avoiding interaction and outreach, which can increase depression and the burden of caregiving.…”
Section: Discussionmentioning
confidence: 99%
“… 27 Moreover, Ahmad et al revealed a significant positive relationship between social support and the quality of life among the caregivers of drug-addicted people. 33 Social relationships were among the most affected aspects of life in the whole family of addicted patients due to reduced opportunities for leisure activities, changes in family routines, and difficulties encountered in working and meeting their colleagues. 33 Moreover, some addicts and caregivers chose social isolation as a tool to safeguard their reputation in society by avoiding interaction and outreach, which can increase depression and the burden of caregiving.…”
Section: Discussionmentioning
confidence: 99%